Directors culture and environmental disclosure practice of companies in Malaysia - Ayoib, Che-Ahmad (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), 2015)
Link to publisher's homepage at http://ijbt.unimap.edu.my/